2010
DOI: 10.1152/ajpheart.00980.2009
|View full text |Cite
|
Sign up to set email alerts
|

The calcineurin-myocyte enhancer factor 2c pathway mediates cardiac hypertrophy induced by endoplasmic reticulum stress in neonatal rat cardiomyocytes

Abstract: The calcineurin-myocyte enhancer factor 2c pathway mediates cardiac hypertrophy induced by endoplasmic reticulum stress in neonatal rat cardiomyocytes. Am J Physiol Heart Circ Physiol 298: H1499 -H1509, 2010. First published March 5, 2010; doi:10.1152/ajpheart.00980.2009.-Endoplasmic reticulum (ER) stress (ERS) is involved in various cardiovascular diseases. Our previous study verified that ERS took part in the development of cardiac hypertrophy; however, its mechanism is still unclear. This study aimed to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 47 publications
(41 reference statements)
2
22
0
Order By: Relevance
“…The CHOP and caspase-12 proteins are distal effectors of ERS response mediating apoptotic signals. There is extensive evidence indicating ERS markers, GRP78 and CHOP are increased in cases of cardiac hypertrophy and incidences of heart failure [25,26]. ERS has been shown to lead to apoptosis in these processes and as a link between apoptosis, cardiomyocyte loss, ventricular remodeling, and deterioration of systolic performance in multiple experimental models [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…The CHOP and caspase-12 proteins are distal effectors of ERS response mediating apoptotic signals. There is extensive evidence indicating ERS markers, GRP78 and CHOP are increased in cases of cardiac hypertrophy and incidences of heart failure [25,26]. ERS has been shown to lead to apoptosis in these processes and as a link between apoptosis, cardiomyocyte loss, ventricular remodeling, and deterioration of systolic performance in multiple experimental models [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…To test whether 14-3-3 protein involved in the ERS response during cardiac ERS through SERCA2, we further induced ERS using thapsigargin. Thapsigargin has been known to inhibit contraction and Ca 2+ transient in cardiac cells by specific inhibition of the SERCA pump [25], to increase protein levels of ER chaperones in cultured cardiac myocytes [5] and to elicit ERS in time and dose-dependent manner in the neonatal rat cardiomyocytes [26]. In our study, we have shown that the inhibition of SERCA2 using thapsigargin significantly increased cardiac expression of GRP78 protein in the DN14-3-3 mice compared with the WT mice.…”
Section: Role Of 14-3-3 Protein In Cardiac Ersmentioning
confidence: 99%
“…The activation of ER stress in the heart is associated with myocardial apoptosis [4,5], hypertrophy [6,7], and fibrosis [8,9], the pathological processes common in development of ischemic and hypertrophic heart diseases. Therefore, inhibiting ER stress may be an important consideration in developing treatments for ischemic or hypertrophic cardiomyopathy.…”
Section: Introductionmentioning
confidence: 99%